2019
DOI: 10.1088/1742-6596/1402/7/077070
|View full text |Cite
|
Sign up to set email alerts
|

Digitalisation trend in education during industry 4.0

Abstract: This study synthesizes the findings of a study of the trend of digitalization of the education world in the face of the industrial revolution 4.0. The researched journal starts from 2015 to 2019. This paper focuses on the challenges and opportunities of industry 4.0, the development of industry 4.0 is characterized by the development of big data and artificial intelligence. Skills needed in this era or called big data and artificial intelligence, including advanced analytics, Internet of Things, and digital se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 13 publications
1
27
0
2
Order By: Relevance
“…Learning through e-learning requires a well-planned design, including those related to the e-learning component (Muktiarni, Widiaty, Abdullah, & Ana, 2019). E-learning must have three basic components consisting of ecommunication (material communication), e-training (LMS system approach) and e-assessment (assessment of learning outcomes indicators) (Donnelly & Mcsweeney, 2008).…”
Section: Fig4 Percentage Of Respondents' Perceptions Regarding E-lementioning
confidence: 99%
“…Learning through e-learning requires a well-planned design, including those related to the e-learning component (Muktiarni, Widiaty, Abdullah, & Ana, 2019). E-learning must have three basic components consisting of ecommunication (material communication), e-training (LMS system approach) and e-assessment (assessment of learning outcomes indicators) (Donnelly & Mcsweeney, 2008).…”
Section: Fig4 Percentage Of Respondents' Perceptions Regarding E-lementioning
confidence: 99%
“…Therefore, scholars from around the world are exploring issues of education and improving its quality, namely: − digital education [4], − a model of a different higher education [5], − digital security [6], − distance learning system [7], − portfolio of vocational education services [8], etc. Having studied the educational direction, the researchers have concluded that there is no formed, recommended structure for the work of educational and methodological support of the educational organization (listeners, teaching employees).…”
Section: Methodsmentioning
confidence: 99%
“…Even if jobs that can be automated and those having low-level skills disappear, it does not prevent the emergence of new jobs that require high-skill activities like planning, control and IT-related tasks necessary for the development, implementation, maintenance and use of new technologies. [16][17], [5].…”
Section: Industry 40 Conceptsmentioning
confidence: 99%